The Association between Atrial Fibrillation and Central Retinal Artery Occlusion: A Meta-Analysis and Systematic Review: Oral Presentation - Observational Study - General practitioner - Yufilia Suci Amelia (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Central retinal artery occlusion (CRAO) is a condition where the central retinal artery is blocked. Atrial Fibrillation (AF) is commonly associated with retinal embolism that originates anywhere between the heart and the ophthalmic artery. This study aims to explore the incidence of AF in CRAO. Methods : A systematic search was performed in three databases: Pubmed, EBSCO host, and Proquest. Newcastle-Ottawa Scale was used to assess the risk of bias in the study included. Results : Our systematic review comprises six studies, 4 studies included CRAO patients as the study population and AF as the endpoint, and the others 2 studies with CRAO as the endpoint. Meta- analysis of the first group resulted in a significantly favorable AF incident after CRAO with an odds ratio (OR) of 1.46 (95% CI 1.17-1.81, p=0.0007). The second meta-analysis supports CRAO with an OR of 4.86 (95% CI 2.30-10.28, p<0.0001). Conclusion : It is crucial to identify AF in preventing ocular infarction. This study revealed that AF was identified as a risk factor in patients with CRAO and vice versa.